Phenotypic detection of inducible clindamycin resistance among Staphylococcus aureus isolates - Nikam, Archana P.; Bhise, Pramod R.; Deshmukh, Mukta M. (International Journal of Research in Medical Sciences, 2017)
Background: Staphylococcus aureus is a leading cause of nosocomial and community acquired infection in every region of world. Clindamycin is a frequent therapeutic option in the treatment of skin and soft tissue infection caused by Staphylococcus aureus. However resistance to this drug is again a problem which may be inducible or constitutive. The present study was carried out to determine the prevalence of inducible clindamycin resistance among Staphylococcus aureus and to find out the relationship between methicillin resistant Staphylococcus aureus and inducible clindamycin resistance. Methods: A total of 177 Staphylococcus aureus isolated from different clinical samples were subjected to routine antibiotic sensitivity testing by Kirby Bauer disc diffusion method. All were tested for Methicillin resistance by using cefoxitin 30 µg disc. Inducible clindamycin resistance was detected by ‘D’ test as per CLSI guidelines. Results: Out of the 177 Staphylococcus aureus isolates, 77 (43.50%) were MRSA and 100 (56.50%) were MSSA. 101 (57.06%) isolates were erythromycin resistant. These erythromycin resistant isolates when subjected to ‘D’ test, 27 isolates showed MS phenotype, 26 showed inducible MLSB phenotype and 48 showed constitutive MLSB phenotype. Out of 77 MRSA isolates 23 (29.87%) showed Inducible MLSB phenotype and 33 (42.85%) showed Constitutive MLSB phenotype, while in 100 methicillin sensitive Staphylococcal isolates 03 (3%) showed Inducible MLSB phenotype and 15 (15%) showed Constitutive MLSB phenotype. The percentage of inducible and constitutive resistance was higher amongst MRSA isolates as compared to MSSA isolates. Conclusions: Study showed that ‘D’ test should be used routinely to detect inducible clindamycin resistance.